Solar observations at the Coimbra Astronomical Observatory - Lourenço, Ana (2019)
In 2020, the Geophysical and Astronomical Observatory of the University of Coimbra will celebrate the 95th anniversary of its first spectroheliographic observation. Keeping a daily service of solar observations since then, making almost a century, led to one of the largest continuous solar data collections in the world. This long–term solar database is essential for studies where solar activity is involved. This work reviews the development of synoptic observations made at the Observatory of Coimbra since 1925 and presents a summary of some of the principal stages of the Observatory’s history since its founding in 1772. We refer the main technical improvements and present some perspectives for the near future. One of the most significant upgrades was the installation of a CCD camera in 2007. The transition from photographic emulsion to digital recording methods allowed the development of image analysis algorithms to process solar images and improved data sharing with other institutions. This upgrade enabled also to carry–out modern climate and space weather studies. This valuable advancement makes it possible to create a new catalogue of solar observations to be published in the future.